Lactobacillus reuteri strain 8008 attenuated the aggravation of depressive-like behavior induced by CUMS in high-fat diet-fed mice through regulating the gut microbiota - Li, Canye; Su, Zuanjun; Chen, Zhicong; Cao, Jinming; Liu, Xiufeng; Xu, Feng (Frontiers in Pharmacology, 2023)
Objective: Gut microbes play a key role in the pathogenesis of obesity and depression. Probiotics are a preventive strategy for obesity and a novel treatment for depression symptoms. However, the ameliorative or therapeutic potential of probiotic Lactobacillus reuteri (L.r) on obesity and depression comorbidity remains unclear. We investigated the effects of Lactobacillus reuteri on various disease indicators of obesity and depression comorbidity disease. Methods: Forty male C57BL/6 mice were randomized into 2 groups: the normal control (NC) group (n=10) and the high-fat diet (HFD) group (n=30), being fed with normal diet (ND) or high-fat diet (HFD) for 8 weeks, respectively. Then the obese mice fed with HFD were randomly allocated into 3 sub-groups: the HFD group (n=10); the HFD+CUMS group (n=10); the HFD+CUMS+L.r group (n=10). The latter 2 subgroups underwent chronic unpredictable mild stress (CUMS) for 4 weeks to build the obesity and depression comorbidity mice model. Meanwhile mice were gavaged with PBS solution or L.r (1×109CFU) once a day, respectively. The body weight, food intake, organ weight, behavioral indicators, histology, blood lipids, levels of inflammatory cytokines and tight junction proteins and abundance of colonic contents bacteria were measured. Results: Obesity and depression comorbidity mice model was successfully established after HFD feeding and chronic stress. The comorbid mice demonstrated inflammatory responses increase in liver and adipose tissues, worsened damage to the intestinal barrier as well as gut microbiota disorder. Gavaged with L.r attenuated depressive-like behavior, reversed the weight loss caused by CUMS, improved blood lipids and insulin resistance, reduced inflammation in liver and adipose tissues, improved intestinal tight junctions as well as the microbiome dysbiosis in obesity and depression comorbidity mice. Conclusion: Lactobacillus reuteri could alleviate depressive-like behaviors and related indicators of obesity disorders by regulating the gut microbiota in obesity and depression comorbid mice.